BIBLICAL THEOLOGY IN ASIA: CONTRIBUTION OF JOSEPH PATHRAPANKAL - Koroth, Pascal (Asian Horizons, 2019)
The churches in Asia have many famous biblical theologians known for their illustrious teaching career, erudite publications and original ideas. Their literary contributions have enriched the treasury of Theology. Some of them have spent their lifetime in the formation of the clergy and the future ministers of the Word. Professor Dr Joseph Pathrapankal CMI (JP) is outstanding among them by reason of his illustrious teaching career, prolific literary contribution, multi-faceted ministry of the Word, dedicated service in different fields of biblical scholarship and Word-centred life. As a biblical theologian, clarity in thought, consistency of views and firmness in opinions are constant features of JP. This article gives a brief sketch of the life of JP, a summary remark about his vast literary contributions and a comment about JP’s dominant theological views. In fact, JP’s illustrious life as a biblical theologian is an eloquent example how a Bible scholar can be both critical and creative in one’s ministry of the Word. This article is also a tribute to this Nonagenarian Bible scholar. It may serve also as a challenge for the new generation scholars to become Word-centred persons so as to inspire the coming generations to involve critically and creatively in the mission of the Church today.